A high corrosion resistance wear-resistant composite plate and preparation method thereof

By hot rolling on the aluminum-based composite board and coating zinc molybdate modified epoxy resin and modified hydroxyacrylic dispersion anticorrosion paint, the problem of insufficient wear resistance of the aluminum-based composite board is solved, and the preparation of high-corrosion-resistant wear-resistant composite board is realized, which significantly improves its anti-corrosion and wear resistance.

CN118544647BActive Publication Date: 2025-02-28JIANGSU WODON WEAR RESISTANT NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410631749.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2025-02-28
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

The existing aluminum-based composite panels have shortcomings in wear resistance, which is difficult to meet the demand for high-corrosion-resistant wear-resistant composite panels in the fields of aerospace, automobiles, etc.

Method used

By pretreating on the aluminum substrate and Ni-Al plate and hot rolling according to a specific stacking method, after forming the composite plate, a layer of zinc molybdate modified epoxy resin anticorrosion primer and modified hydroxyacrylic dispersion anticorrosion topcoat are coated on the surface to form a high-corrosion-resistant wear-resistant composite plate.

Benefits of technology

It significantly improves the corrosion resistance and wear resistance of composite boards, can more effectively resist external corrosion factors and wear, and meets the application needs of high-corrosion-resistant wear-resistant composite boards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a highly corrosion-resistant wear-resistant composite plate and a preparation method thereof, and belongs to the technical field of plate materials. An aluminum substrate and a Ni-Al plate are prepared, pre-treated, and stacked in a manner of a middle Ni-Al plate and upper and lower aluminum substrates, fixed by rivets for hot-rolling and compounding to obtain a composite plate, polished, washed and dried, a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the side, cured, and then a layer of anti-corrosion topcoat is applied and cured to obtain a highly corrosion-resistant wear-resistant composite plate, wherein the anti-corrosion primer contains substances such as modified epoxy resin, and the anti-corrosion primer contains substances such as modified hydroxyl acrylic acid dispersion, and the two types of film layers improve the corrosion resistance and wear resistance of the composite plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plates, in particular to a highly corrosion-resistant wear-resistant composite plate and a preparation method thereof. Background Art

[0002] With the rapid development of human society and economy, metal materials with a single component are difficult to meet the stringent environmental requirements. Driven by market demand, the metal composite sheet industry has developed rapidly. Composite panels are processed by combining different metal plates, combining the properties of both substrate and cover materials, greatly improving the strength, toughness, corrosion resistance and other properties of single metal materials, and are widely used in building curtain walls, interior decoration, vehicle shells, electricity, petroleum and other fields.

[0003] Aluminum-based composite plates have the advantages of corrosion resistance, good mechanical properties, and easy processing, which have attracted widespread attention. However, they also have disadvantages such as poor wear resistance. With the development of aerospace, automotive, electronics and other fields, in order to meet market demand, the requirements for composite plate aluminum materials are increasing. Therefore, there is an urgent need to find a highly corrosion-resistant and wear-resistant composite plate to meet future challenges. Summary of the invention

[0004] The object of the present invention is to provide a highly corrosion-resistant wear-resistant composite plate and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a highly corrosion-resistant wear-resistant composite plate, the specific preparation steps are as follows:

[0007] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400-450°C for 10-15 minutes, roll them until the deformation is 60-80%, anneal them at a temperature of 450-500°C for 10-20 minutes, wash and dry them, and obtain a composite plate;

[0008] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 to 0.2 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.1 to 0.2 mm, to obtain the highly anti-corrosion wear-resistant composite plate.

[0009] The preparation steps of the Ni-Al plate include: taking Ni powder and aluminum alloy powder, adding graphite powder in a mass ratio of 1:1, mechanically mixing, placing the mixed Ni-Al powder in a mold for sintering, and obtaining a Ni-Al plate, wherein the chemical compositions of the aluminum alloy powder and the aluminum substrate are: in mass fraction, 0.65-0.95% Si, 0.5-0.8% Fe, 0.01-0.05% Cu, 0.01-0.05% Mn, 0.05-0.08% Mg, 0.02-0.05% Zn, and the balance is Al; and the sintering parameters are: a heating rate of 10°C / min, heating to 650-700°C, and keeping warm for 1-2h.

[0010] The components of the anti-corrosion primer include, by mass percentage, 25-45% of zinc molybdate modified epoxy resin, 10-15% of solvent, 0.5-1% of dispersant, 0.1-0.2% of silicone defoamer, 20-30% of filler, 15-20% of anti-rust pigment, 0.5-1% of organic bentonite, 0.1-0.5% of silane coupling agent, and 5-10% of phenolic amine curing agent; wherein the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust filler includes: the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0011] The preparation steps of zinc molybdate modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water, obtaining a 1-2 mg / mL uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate into deionized water to prepare a zinc acetate solution, adding the zinc acetate solution into the graphene oxide dispersion under stirring, and stirring for 5-6 hours; adding ammonium molybdate tetrahydrate into deionized water to prepare a 0.01-0.02 mol / L ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 5-6 hours to obtain the zinc molybdate modified epoxy resin, wherein the mass ratio of the composite material to the epoxy resin is 1:100.

[0012] The components of the anti-corrosion topcoat include, by mass percentage, 30-40% of modified hydroxy acrylic dispersion, 15-30% of deionized water, 5-10% of modified nano titanium dioxide, 5-10% of anti-rust pigment, 0.1-0.5% of thickener, 5-13% of silicone defoamer, 5-15% of dispersant, 5-10% of cosolvent, 1-5% of anti-flash rust agent, and 10-20% of isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, with a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the cosolvent is isopropyl alcohol and 1-methyl-pyrrolidone, with a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0013] The preparation steps of the modified hydroxy acrylic dispersion are as follows: 30g of epoxy resin and 8g of propylene glycol methyl ether are heated to 125°C, 10g of isooctanoic acid and 0.01g of tetramethylammonium chloride are added, stirred, kept warm for 4h, cooled to 100°C, and epoxy resin mixed solution is obtained for standby use; 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, and then 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, stirred evenly, and slowly stirred. Slowly add it to the above epoxy resin mixture, keep warm for 30 minutes, add 2g of benzoyl perchloride, and keep warm for 1.5-2h; cool to 85°C, add 10g of triethanolamine, react for 30 minutes, add 120mL of deionized water, disperse for 30 minutes, add organic fluorine / silicon compound, blend, and obtain a modified hydroxy acrylic dispersion, wherein the organic fluorine / silicon compound is 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; the organic fluorine / silicon compound is 0.3-0.5wt% of the total system.

[0014] The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 2 to 3 hours, dry and grind to obtain modified nano titanium dioxide; wherein the mass ratio of silane coupling agent to titanium dioxide is 1:5.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: after the hot-rolled composite plate is coated with a layer of anti-corrosion primer and anti-corrosion topcoat on the surface, a highly anti-corrosion and wear-resistant composite plate is obtained; the epoxy resin is modified in the anti-corrosion primer, and graphene oxide and zinc molybdate are added as a functional filler to the epoxy resin; graphene oxide improves the dispersibility of zinc molybdate, and zinc molybdate delays the penetration of external corrosion factors, cooperates with the anti-corrosion pigment in the primer, and establishes a barrier that effectively isolates the corrosive medium, further improving the anti-corrosion performance of the primer coating; the modified hydroxyl acrylic dispersion in the anti-corrosion topcoat has good adhesion and corrosion resistance, and the added organic fluorine / silicon compound can well improve the wear resistance; the addition of modified nano titanium dioxide greatly improves its dispersibility in the topcoat, and improves the anti-corrosion performance of the topcoat to a certain extent; the primer and the topcoat work together to improve the anti-corrosion and wear resistance of the composite plate. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] In the experiment, the flake size of graphite powder is 0.5-1mm; the dispersant is BYK-110; the silicone defoamer is TEGOFoamex 8030; the organic bentonite is BYK MP100; the silane coupling agent is KH570; the phenolic amine curing agent is T-60, purchased from Shanghai SuoShi Chemical Co., Ltd.; the particle size of aluminum tripolyphosphate is 325-1000 mesh; the lateral size of graphene oxide is 0.5-10μm; the nano titanium dioxide is CR-50; the isocyanate curing agent is Aquolin269, purchased from Fujian Liantuo Blueprint Materials Technology Co., Ltd.; and the epoxy resin is E-20.

[0018] The preparation steps of the Ni-Al plate include: taking Ni powder and aluminum alloy powder, adding graphite powder according to a mass ratio of 1:1, mechanically mixing, placing the mixed Ni-Al powder in a mold for sintering, and obtaining a Ni-Al plate, wherein the chemical compositions of the aluminum alloy powder and the aluminum substrate are: in mass fraction, 0.95% Si, 0.8% Fe, 0.05% Cu, 0.05% Mn, 0.08% Mg, 0.05% Zn, and the balance is Al; and the sintering parameters are: a heating rate of 10°C / min, heating to 650°C, and keeping warm for 2h.

[0019] Embodiment 1: This embodiment provides a method for preparing a highly corrosion-resistant wear-resistant composite plate, and the specific steps are as follows:

[0020] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400°C for 15 minutes, roll them until the deformation is 70%, anneal them at 500°C for 10 minutes, wash and dry them, and obtain a composite plate;

[0021] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.15 mm, thereby obtaining the highly anti-corrosion wear-resistant composite plate.

[0022] The components of the anti-corrosion primer include, by mass percentage, 40% zinc molybdate modified epoxy resin, 13% solvent, 1% dispersant, 0.2% silicone defoamer, 20% filler, 15% anti-rust pigment, 0.5% organic bentonite, 0.3% silane coupling agent, and 10% phenolic amine curing agent; the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust pigment includes zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0023] The preparation steps of zinc molybdate modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water, obtaining a 1 mg / mL uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate to deionized water to prepare a zinc acetate solution, adding the zinc acetate solution to the graphene oxide dispersion under stirring, and stirring for 6 hours; adding ammonium molybdate tetrahydrate to deionized water to prepare a 0.02 mol / L ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 6 hours to obtain the zinc molybdate modified epoxy resin, wherein the mass ratio of the composite material to the epoxy resin is 1:100.

[0024] The components of the anti-corrosion topcoat include, in mass percentage, 30% modified hydroxy acrylic dispersion, 20% deionized water, 6% modified nano titanium dioxide, 6% anti-rust pigment, 2% thickener, 8% silicone defoamer, 6% dispersant, 5% co-solvent, 2% anti-flash rust agent, and 15% isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, in a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the co-solvent is isopropyl alcohol and 1-methyl-pyrrolidone, in a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0025] The preparation steps of the modified hydroxy acrylic dispersion are as follows: 30g of epoxy resin and 8g of propylene glycol methyl ether are heated to 125°C, 10g of isooctanoic acid and 0.01g of tetramethylammonium chloride are added, stirred, kept warm for 4h, cooled to 100°C, and epoxy resin mixed solution is obtained for standby use; 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, and stirred evenly. The mixture was uniformly added and slowly dropped into the epoxy resin mixture, and kept warm for 30 minutes. 2 g of benzoyl perchloride was added and kept warm for 1.5 hours. The temperature was lowered to 85°C, 10 g of triethanolamine was added, and the mixture was reacted for 30 minutes. 120 mL of deionized water was added and the mixture was dispersed for 30 minutes. An organic fluorine / silicon compound was added and the mixture was blended to obtain a modified hydroxy acrylic dispersion, wherein the organic fluorine / silicon compound was 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; the organic fluorine / silicon compound accounted for 0.3 wt% of the total system.

[0026] The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 3 hours, dry and grind to obtain nano titanium dioxide; wherein the mass ratio of silane coupling agent to nano titanium dioxide is 1:5.

[0027] Embodiment 2: This embodiment provides a method for preparing a highly corrosion-resistant wear-resistant composite plate, and the specific steps are as follows:

[0028] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400°C for 15 minutes, roll them until the deformation is 70%, anneal them at 500°C for 10 minutes, wash and dry them, and obtain a composite plate;

[0029] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.15 mm, thereby obtaining the highly anti-corrosion wear-resistant composite plate.

[0030] The components of the anti-corrosion primer include, by mass percentage, 42% zinc molybdate modified epoxy resin, 13% solvent, 1% dispersant, 0.2% silicone defoamer, 18% filler, 15% anti-rust pigment, 0.5% organic bentonite, 0.3% silane coupling agent, and 10% phenolic amine curing agent; the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust pigment includes zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0031] The preparation steps of zinc molybdate modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water, obtaining a 1 mg / mL uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate to deionized water to prepare a zinc acetate solution, adding the zinc acetate solution to the graphene oxide dispersion under stirring, and stirring for 6 hours; adding ammonium molybdate tetrahydrate to deionized water to prepare a 0.02 mol / L ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 6 hours to obtain the zinc molybdate modified epoxy resin, wherein the mass ratio of the composite material to the epoxy resin is 1:100.

[0032] The components of the anti-corrosion topcoat include, in mass percentage, 35% modified hydroxy acrylic dispersion, 18% deionized water, 6% modified nano titanium dioxide, 6% anti-rust pigment, 2% thickener, 8% silicone defoamer, 6% dispersant, 5% co-solvent, 2% anti-flash rust agent, and 12% isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, in a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the co-solvent is isopropyl alcohol and 1-methyl-pyrrolidone, in a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0033] The preparation steps of the modified hydroxy acrylic dispersion are as follows: 30g of epoxy resin and 8g of propylene glycol methyl ether are heated to 125°C, 10g of isooctanoic acid and 0.01g of tetramethylammonium chloride are added, stirred, kept warm for 4h, cooled to 100°C, and epoxy resin mixed solution is obtained for standby use; 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, and stirred evenly. The mixture was uniformly added and slowly dropped into the epoxy resin mixture, and kept warm for 30 minutes. 2 g of benzoyl perchloride was added and kept warm for 1.5 hours. The temperature was lowered to 85°C, 10 g of triethanolamine was added, and the mixture was reacted for 30 minutes. 120 mL of deionized water was added and the mixture was dispersed for 30 minutes. An organic fluorine / silicon compound was added and the mixture was blended to obtain a modified hydroxy acrylic dispersion, wherein the organic fluorine / silicon compound was 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; the organic fluorine / silicon compound accounted for 0.5 wt% of the total system.

[0034] The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 3 hours, dry and grind to obtain nano titanium dioxide; wherein the mass ratio of silane coupling agent to nano titanium dioxide is 1:5.

[0035] Embodiment 3: This embodiment provides a method for preparing a highly corrosion-resistant wear-resistant composite plate, and the specific steps are as follows:

[0036] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400°C for 15 minutes, roll them until the deformation is 70%, anneal them at 500°C for 10 minutes, wash and dry them, and obtain a composite plate;

[0037] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.15 mm, thereby obtaining the highly anti-corrosion wear-resistant composite plate.

[0038] The components of the anti-corrosion primer include, by mass percentage, 45% zinc molybdate modified epoxy resin, 10% solvent, 1% dispersant, 0.2% silicone defoamer, 18% filler, 15% anti-rust pigment, 0.5% organic bentonite, 0.3% silane coupling agent, and 10% phenolic amine curing agent; the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust pigment includes zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0039] The preparation steps of zinc molybdate modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water, obtaining a 1 mg / mL uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate to deionized water to prepare a zinc acetate solution, adding the zinc acetate solution to the graphene oxide dispersion under stirring, and stirring for 6 hours; adding ammonium molybdate tetrahydrate to deionized water to prepare a 0.02 mol / L ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 6 hours to obtain the zinc molybdate modified epoxy resin, wherein the mass ratio of the composite material to the epoxy resin is 1:100.

[0040] The components of the anti-corrosion topcoat include, in mass percentage, 38% modified hydroxy acrylic dispersion, 16% deionized water, 7% modified nano titanium dioxide, 6% anti-rust pigment, 2% thickener, 6% silicone defoamer, 6% dispersant, 5% co-solvent, 2% anti-flash rust agent, and 12% isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, in a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the co-solvent is isopropyl alcohol and 1-methyl-pyrrolidone, in a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0041] The preparation steps of the modified hydroxy acrylic dispersion are as follows: 30g of epoxy resin and 8g of propylene glycol methyl ether are heated to 125°C, 10g of isooctanoic acid and 0.01g of tetramethylammonium chloride are added, stirred, kept warm for 4h, cooled to 100°C, and epoxy resin mixed solution is obtained for standby use; 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, and stirred evenly. The mixture was uniformly added and slowly dropped into the epoxy resin mixture, and kept warm for 30 minutes. 2 g of benzoyl perchloride was added and kept warm for 1.5 hours. The temperature was lowered to 85°C, 10 g of triethanolamine was added, and the mixture was reacted for 30 minutes. 120 mL of deionized water was added and the mixture was dispersed for 30 minutes. An organic fluorine / silicon compound was added and the mixture was blended to obtain a modified hydroxy acrylic dispersion, wherein the organic fluorine / silicon compound was 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; the organic fluorine / silicon compound accounted for 0.5 wt% of the total system.

[0042] The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 3 hours, dry and grind to obtain nano titanium dioxide; wherein the mass ratio of silane coupling agent to nano titanium dioxide is 1:5.

[0043] Comparative Example 1: Comparative Example 1 is a control experiment of Example 3, and the zinc molybdate-modified epoxy resin in Example 3 is not modified. The specific steps are as follows:

[0044] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400°C for 15 minutes, roll them until the deformation is 70%, anneal them at 500°C for 10 minutes, wash and dry them, and obtain a composite plate;

[0045] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.15 mm, thereby obtaining the highly anti-corrosion wear-resistant composite plate.

[0046] The components of the anti-corrosion primer include, by mass percentage, 45% epoxy resin, 10% solvent, 1% dispersant, 0.2% silicone defoamer, 18% filler, 15% anti-rust pigment, 0.5% organic bentonite, 0.3% silane coupling agent, and 10% phenolic amine curing agent; the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust pigment includes zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0047] The components of the anti-corrosion topcoat include, in mass percentage, 38% modified hydroxy acrylic dispersion, 16% deionized water, 7% modified nano titanium dioxide, 6% anti-rust pigment, 2% thickener, 6% silicone defoamer, 6% dispersant, 5% co-solvent, 2% anti-flash rust agent, and 12% isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, in a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the co-solvent is isopropyl alcohol and 1-methyl-pyrrolidone, in a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0048] The preparation steps of the modified hydroxy acrylic dispersion are as follows: 30g of epoxy resin and 8g of propylene glycol methyl ether are heated to 125°C, 10g of isooctanoic acid and 0.01g of tetramethylammonium chloride are added, stirred, kept warm for 4h, cooled to 100°C, and epoxy resin mixed solution is obtained for standby use; 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, and stirred evenly. The mixture was uniformly added and slowly dropped into the epoxy resin mixture, and kept warm for 30 minutes. 2 g of benzoyl perchloride was added and kept warm for 1.5 hours. The temperature was lowered to 85°C, 10 g of triethanolamine was added, and the mixture was reacted for 30 minutes. 120 mL of deionized water was added and the mixture was dispersed for 30 minutes. An organic fluorine / silicon compound was added and the mixture was blended to obtain a modified hydroxy acrylic dispersion, wherein the organic fluorine / silicon compound was 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; the organic fluorine / silicon compound accounted for 0.5 wt% of the total system.

[0049] The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 3 hours, dry and grind to obtain nano titanium dioxide; wherein the mass ratio of silane coupling agent to nano titanium dioxide is 1:5.

[0050] Comparative Example 2: Comparative Example 2 is a control experiment of Example 3, in which the modified nano titanium dioxide in Example 3 is replaced with nano titanium dioxide, and the specific steps are as follows:

[0051] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400°C for 15 minutes, roll them until the deformation is 70%, anneal them at 500°C for 10 minutes, wash and dry them, and obtain a composite plate;

[0052] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.15 mm, thereby obtaining the highly anti-corrosion wear-resistant composite plate.

[0053] The components of the anti-corrosion primer include, by mass percentage, 45% zinc molybdate modified epoxy resin, 10% solvent, 1% dispersant, 0.2% silicone defoamer, 18% filler, 15% anti-rust pigment, 0.5% organic bentonite, 0.3% silane coupling agent, and 10% phenolic amine curing agent; the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust pigment includes zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0054] The preparation steps of zinc molybdate modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water, obtaining a 1 mg / mL uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate to deionized water to prepare a zinc acetate solution, adding the zinc acetate solution to the graphene oxide dispersion under stirring, and stirring for 6 hours; adding ammonium molybdate tetrahydrate to deionized water to prepare a 0.02 mol / L ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 6 hours to obtain the zinc molybdate modified epoxy resin, wherein the mass ratio of the composite material to the epoxy resin is 1:100.

[0055] The components of the anti-corrosion topcoat include, in percentage by mass, 38% modified hydroxy acrylic dispersion, 16% deionized water, 7% nano titanium dioxide, 6% anti-rust pigment, 2% thickener, 6% silicone defoamer, 6% dispersant, 5% co-solvent, 2% anti-flash rust agent, and 12% isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, in a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the co-solvent is isopropyl alcohol and 1-methyl-pyrrolidone, in a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0056] The preparation steps of the modified hydroxy acrylic dispersion are as follows: 30g of epoxy resin and 8g of propylene glycol methyl ether are heated to 125°C, 10g of isooctanoic acid and 0.01g of tetramethylammonium chloride are added, stirred, kept warm for 4h, cooled to 100°C, and epoxy resin mixed solution is obtained for standby use; 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, and stirred evenly. The mixture was uniformly added and slowly dropped into the epoxy resin mixture, and kept warm for 30 minutes. 2 g of benzoyl perchloride was added and kept warm for 1.5 hours. The temperature was lowered to 85°C, 10 g of triethanolamine was added, and the mixture was reacted for 30 minutes. 120 mL of deionized water was added and the mixture was dispersed for 30 minutes. An organic fluorine / silicon compound was added and the mixture was blended to obtain a modified hydroxy acrylic dispersion, wherein the organic fluorine / silicon compound was 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; the organic fluorine / silicon compound accounted for 0.5 wt% of the total system.

[0057] Comparative Example 3: Comparative Example 3 is a control experiment of Example 3. The modified hydroxylated acrylic dispersion in Example 3 is not modified with epoxy resin and organic fluorine / silicon compound. The specific steps are as follows:

[0058] Step 1: Prepare an aluminum substrate and a Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is a Ni-Al plate and the upper and lower layers are aluminum substrates, fix them with rivets, keep them at 400°C for 15 minutes, roll them until the deformation is 70%, anneal them at 500°C for 10 minutes, wash and dry them, and obtain a composite plate;

[0059] Step 2: The composite plate obtained in step 2 is polished, washed and dried, and a layer of anti-corrosion primer is sprayed on the upper and lower surfaces and the sides, and the film thickness of the cured anti-corrosion primer is 0.1 mm. Then a layer of anti-corrosion topcoat is applied, and the film thickness of the cured anti-corrosion topcoat is 0.15 mm, thereby obtaining the highly anti-corrosion wear-resistant composite plate.

[0060] The components of the anti-corrosion primer include, by mass percentage, 45% zinc molybdate modified epoxy resin, 10% solvent, 1% dispersant, 0.2% silicone defoamer, 18% filler, 15% anti-rust pigment, 0.5% organic bentonite, 0.3% silane coupling agent, and 10% phenolic amine curing agent; the solvent includes xylene and butanol in a mass ratio of 2:1; the filler includes talcum powder and feldspar powder in a mass ratio of 1:1; the anti-rust pigment includes zinc phosphomolybdate and aluminum tripolyphosphate in a mass ratio of 1:1.

[0061] The preparation steps of zinc molybdate modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water, obtaining a 1 mg / mL uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate to deionized water to prepare a zinc acetate solution, adding the zinc acetate solution to the graphene oxide dispersion under stirring, and stirring for 6 hours; adding ammonium molybdate tetrahydrate to deionized water to prepare a 0.02 mol / L ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 6 hours to obtain the zinc molybdate modified epoxy resin, wherein the mass ratio of the composite material to the epoxy resin is 1:100.

[0062] The components of the anti-corrosion topcoat include, in percentage by mass, 38% hydroxy acrylic dispersion, 16% deionized water, 7% modified nano titanium dioxide, 6% anti-rust pigment, 2% thickener, 6% silicone defoamer, 6% dispersant, 5% cosolvent, 2% anti-flash rust agent, and 12% isocyanate curing agent; the anti-rust pigment includes: zinc phosphomolybdate and aluminum tripolyphosphate, in a mass ratio of 1:1; the thickener is hydroxyethyl cellulose; the cosolvent is isopropyl alcohol and 1-methyl-pyrrolidone, in a mass ratio of 1:1; the anti-flash rust agent is sodium nitrite.

[0063] The preparation steps of the hydroxy acrylic dispersion are as follows: 8g of methyl methacrylate, 5g of styrene, 10g of n-butyl acrylate, 5g of acrylic acid and 8g of hydroxyethyl methacrylate are mixed as monomers, and then 2g of benzoyl peroxide, 8g of propylene glycol methyl ether and 4g of ethylene glycol butyl ether are added in sequence, mixed, stirred evenly, 2g of benzoyl perchloride is added, and the mixture is kept warm for 1.5h; the temperature is lowered to 85°C, 10g of triethanolamine is added, the reaction is carried out for 30min, 120mL of deionized water is added, and the mixture is dispersed for 30min to obtain a modified hydroxy acrylic dispersion.

[0064] The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 3 hours, dry and grind to obtain nano titanium dioxide; wherein the mass ratio of silane coupling agent to nano titanium dioxide is 1:5.

[0065] Detection experiment

[0066] 1. Hardness test: According to GB / T 6739-2022, take the composite board samples prepared in Examples 1-3 and Comparative Examples 1-3, press the pencil lead downward on the paint film surface at an angle of 45°, push the pencil with a load of 7.5N, and gradually increase the hardness of the pencil until visible defects appear on the paint film surface. The pencil with the highest hardness without defects is taken as the pencil hardness of the paint film and recorded.

[0067] 2. Adhesion test: According to GB / T 9286-2021, the composite board samples prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to a cross-cut test. Six parallel scratches were cut on the surface of the film layer, and six scratches were cut in a direction perpendicular to the six parallel scratches.

[0068] Parallel incisions are made with a grid spacing of 3 mm. After removing loose smear debris, visual inspection is performed and compared with the six-level grading standard.

[0069] 3. Salt spray resistance test: According to GB / T 1771-2007, a neutral salt spray resistance test was performed. The composite board samples prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to diagonal scratch treatment and placed in a salt spray chamber. The temperature in the salt spray chamber was 35°C, the average collection rate of the salt spray solution was 1-2.5 mL / h, the concentration of the collected sodium chloride was 60 g / L, the observation period was 12 h, and the time when scratches and rust appeared was recorded.

[0070] project hardness Adhesion grade Salt spray resistance time Example 1 3H Level 0 1200h Example 2 3H Level 0 1320h Example 3 3H Level 0 1440h Comparative Example 1 3H Level 1 1080h Comparative Example 2 2H Level 0 1104h Comparative Example 3 2H Level 0 960h

[0071] According to the above experimental data, the performance of Example 3 among Examples 1-3 is the best. According to Example 3, three groups of comparative examples were carried out. In Comparative Example 1, the zinc molybdate-modified epoxy resin in Example 3 was not modified, and the adhesion and corrosion resistance were reduced; in Comparative Example 2, the modified nano titanium dioxide in Example 3 was replaced with nano titanium dioxide; in Comparative Example 3, the modified hydroxylated acrylic acid dispersion in Example 3 was not modified, and the corrosion resistance was worse than that of the other two groups of comparative examples.

[0072] Conclusion: The present invention discloses a highly corrosion-resistant wear-resistant composite plate and a preparation method thereof. The scheme design is reasonable, the parameters of each step are appropriate, and the prepared composite plate has excellent corrosion resistance.

[0073] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly corrosion-resistant wear-resistant composite plate, characterized in that: The preparation steps are as follows: Step 1: Prepare the aluminum substrate and the Ni-Al plate, perform pretreatment, stack them in a manner that the middle layer is the Ni-Al plate and the upper and lower layers are the aluminum substrates, fix them with rivets, keep them at 400-450°C for 10-15 minutes, roll them, perform annealing heat treatment, wash and dry them, and obtain a composite plate; Step 2: polishing, washing and drying the composite plate obtained in step 1, spraying a layer of anti-corrosion primer on the upper and lower surfaces and the sides, curing, and then applying a layer of anti-corrosion topcoat, curing, to obtain the highly anti-corrosion wear-resistant composite plate; The components of the anticorrosive primer include: in terms of mass percentage, 25-45% zinc molybdate modified epoxy resin, 10-15% solvent, 0.5-1% dispersant, 0.1-0.2% organosilicon defoamer, 20-30% filler, 15-20% antirust pigment, 0.5-1% organobentonite, 0.1-0.5% silane coupling agent, and 5-10% phenolic amine curing agent; The preparation steps of the zinc molybdate-modified epoxy resin include: taking graphene oxide, ultrasonically dispersing it in deionized water to obtain a uniform graphene oxide dispersion, and setting it aside; adding zinc acetate dihydrate to deionized water to prepare a zinc acetate solution, adding the zinc acetate solution to the graphene oxide dispersion under stirring, and stirring for 5 to 6 hours; adding ammonium molybdate tetrahydrate to deionized water to prepare an ammonium molybdate solution, and dropping it into an ammonium acetate / graphene oxide mixed solution, dropping ammonia water, adjusting the pH to 8, filtering, washing, and drying to obtain a zinc molybdate / graphene oxide composite material; dispersing the obtained composite material in deionized water, adding epoxy resin, and stirring for 5 to 6 hours to obtain the zinc molybdate-modified epoxy resin; The components of the anticorrosive topcoat include: in percentage by mass, 30-40% of modified hydroxyl acrylic dispersion, 15-30% of deionized water, 5-10% of modified nano titanium dioxide, 5-10% of antirust pigment, 1-5% of thickener, 5-13% of organosilicon defoamer, 5-15% of dispersant, 5-10% of cosolvent, 1-5% of anti-flash rust agent, and 10-20% of isocyanate curing agent; The preparation steps of the modified hydroxy acrylic acid dispersion are as follows: take epoxy resin and propylene glycol methyl ether, heat to 125°C, add isooctanoic acid and tetramethylammonium chloride, stir, keep warm for 4 hours, cool to 100°C, obtain epoxy resin mixed solution, and set aside; mix methyl methacrylate, styrene, n-butyl acrylate, acrylic acid, hydroxyethyl methacrylate, benzoyl peroxide, propylene glycol methyl ether and ethylene glycol butyl ether, stir evenly, slowly dropwise add to the above epoxy resin mixed solution, keep warm for 30 minutes, add benzoyl perchloride, and keep warm for 1.5 to 2 hours; cool to 85°C, add triethanolamine, react for 30 minutes, add deionized water, disperse for 30 minutes, add organic fluorine / silicon compound, blend, and obtain modified hydroxy acrylic acid dispersion; The preparation steps of modified nano titanium dioxide are as follows: take nano titanium dioxide, add ethanol, ultrasonically disperse for 15 minutes, stir in a water bath at 80°C, add silane coupling agent, react for 2-3 hours, dry and grind to obtain modified nano titanium dioxide; wherein the mass ratio of silane coupling agent to nano titanium dioxide is 1:

5.

2. The method for preparing a highly corrosion-resistant wear-resistant composite plate according to claim 1, characterized in that: The preparation steps of the Ni-Al plate include: taking Ni powder and aluminum alloy powder, adding graphite powder according to a mass ratio of 1:1, mechanically mixing, placing the mixed Ni-Al powder in a mold for sintering, and obtaining a Ni-Al plate, wherein the chemical compositions of the aluminum alloy powder and the aluminum substrate are: in terms of mass fraction, 0.65-0.95% Si, 0.5-0.8% Fe, 0.01-0.05% Cu, 0.01-0.05% Mn, 0.05-0.08% Mg, 0.02-0.05% Zn, and the balance is Al; and the sintering parameters are: a heating rate of 10°C / min, heating to 650-700°C, and keeping warm for 1-2h.

3. The method for preparing a highly corrosion-resistant wear-resistant composite plate according to claim 1, characterized in that: The rolling deformation is 60~80%, the annealing temperature is 450~500℃, and the annealing time is 10~20min.

4. The method for preparing a highly corrosion-resistant wear-resistant composite plate according to claim 1, characterized in that: The thickness of the anti-corrosion primer is 0.1~0.2mm, and the thickness of the anti-corrosion topcoat is 0.1~0.2mm.

Citation Information

Patent Citations

  • Application of metal composite plate with intermetallic compounds.

    CN107031140A

  • Waterborne epoxy modified acrylic acid insulation varnish as well as preparation and application thereof

    CN107418355A